2020
DOI: 10.1007/s40430-020-02601-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on utilizing hybrid-type nanofluid in plate heat exchangers with different number of plates

Abstract: Different methods have been utilized to enhance the thermal efficiency of the heat exchangers (HEs). A widely used method to upgrade the thermal efficiency of HEs is upgrading the thermal properties of working fluid by utilizing nanoparticles. In this study, Al 2 O 3 and CuO have been utilized to prepare Al 2 O 3-CuO/water hybrid nanofluid. Accordingly, Al 2 O 3 and CuO nanoparticles have been mixed into the water with 1% (50:50) weight concentration. The main objective of this work is testing the prepared hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Tiwari et al (2014) performed CFD based analysis using corrugated PHE to validate the experimental data for different concentrations, temperatures and flow rates by considering CeO 2 /water nanofluids as single phase homogeneous mixture. Gürbüz et al (2020a) reported experimental study to improve thermal efficiency of PHE by improving thermal performance of conventional fluid and varying the number of plates. They observed enhancement in OHTC and effectiveness of PHE by 20% and 16%, Compact plate heat exchanger respectively, for 16 plates.…”
Section: Introductionmentioning
confidence: 99%
“…Tiwari et al (2014) performed CFD based analysis using corrugated PHE to validate the experimental data for different concentrations, temperatures and flow rates by considering CeO 2 /water nanofluids as single phase homogeneous mixture. Gürbüz et al (2020a) reported experimental study to improve thermal efficiency of PHE by improving thermal performance of conventional fluid and varying the number of plates. They observed enhancement in OHTC and effectiveness of PHE by 20% and 16%, Compact plate heat exchanger respectively, for 16 plates.…”
Section: Introductionmentioning
confidence: 99%
“…Each channel in the PHEs has an equivalent flow area. The following equations can be used for obtaining wetted perimeter (Gürbüz et al, 2020):…”
Section: Plate Heat Exchangermentioning
confidence: 99%
“…In some studies, TiO 2 and Al 2 O 3 containing single nanofluids numerically and experimentally were investigated. In addition, during recent years, hybrid-type nanofluids are used to attain superior thermal efficiency(Gürbüz et al, 2020). In the present work, TiO 2 and Al 2 O 3 have been used to produce TiO 2 -Al 2 O 3 /water hybrid nanofluid.…”
mentioning
confidence: 99%
“…Khanlari, Sözen, and Variyenli (2019) reported that using TiO 2 /water nanofluids improved the mean overall heat transfer coefficient in PHE by 6–10%. Similarly, Gürbüz, Sözen, Variyenli, Khanlari, and Tuncer (2020) used Al 2 O 3 ‐CuO/water hybrid nanofluid to enhance the thermal efficiency of heat exchangers. The highest increment in overall heat transfer coefficient was obtained as 12, 19, and 20% in PHEs with 8, 12, and 16 plates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gürbüz, Sözen, Variyenli, Khanlari, and Tuncer (2020) used Al 2 O 3 -CuO/water hybrid nanofluid to enhance the thermal efficiency of heat exchangers. The highest increment in overall heat transfer coefficient was obtained as 12, 19, and 20% in PHEs with 8, 12, and 16 plates, respectively.…”
Section: Introductionmentioning
confidence: 99%